Mutations of the Electron Transport Chain Affect Lifespan and ROS Levels in C. elegans - Fanni Ősz; Aamir Nazir; Krisztina Takács-Vellai; Zsolt Farkas (Antioxidants)
Mutations in highly conserved genes encoding components of the electron transport chain (ETC) provide valuable insights into the mechanisms of oxidative stress and mitochondrial ROS (mtROS) in a wide range of diseases, including cancer, neurodegenerative disorders, and aging. This review explores the structure and function of the ETC in the context of its role in mtROS generation and regulation, emphasizing its dual roles in cellular damage and signaling. Using Caenorhabditis elegans as a model organism, we discuss how ETC mutations manifest as developmental abnormalities, lifespan alterations, and changes in mtROS levels. We highlight the utility of redox sensors in C. elegans for in vivo studies of reactive oxygen species, offering both quantitative and qualitative insights. Finally, we examine the potential of C. elegans as a platform for testing ETC-targeting drug candidates, including OXPHOS inhibitors, which represent promising avenues in cancer therapeutics. This review underscores the translational relevance of ETC research in C. elegans, bridging fundamental biology and therapeutic innovation.